General practice responses to opioid prescribing feedback: a qualitative process evaluation - Wood, Su; Foy, Robbie; Willis, T A; Carder, Paul; Johnson, Stella; Alderson, Sarah (British journal of general practice, 2021)
The rise in opioid prescribing in primary care represents a significant public health challenge, associated with increased psychosocial problems, hospitalisations and mortality. We developed and implemented an evidence-based bi-monthly feedback intervention to reduce opioid prescribing targeting 316 general practices in West Yorkshire over one year. To understand how general practice staff received and responded to the feedback intervention. Qualitative process evaluation involving semi-structured interviews, guided by Normalisation Process Theory (NPT), of primary care healthcare professionals targeted by feedback. We purposively recruited participants according to baseline opioid prescribing levels and degree of change following feedback. Interview data were coded to NPT constructs, and thematically analysed. We interviewed 21 staff from 20 practices. Reducing opioid prescribing was recognised as a priority. Whilst high achievers had clear structures for quality improvement, feedback encouraged some less structured practices to embed changes. The non-prescriptive nature of the feedback reports allowed practices to develop strategies consistent with their own ways of working and existing resources. Practice concerns were allayed by the credibility of the reports and positive experiences of reducing opioid prescribing. The scale, frequency and duration of feedback may have ensured a good overall level of practice population reach. The intervention engaged general practice staff in change by targeting an issue of emerging concern and allowing adaption to different ways of working. Practice efforts to reduce opioid prescribing were reinforced by regular feedback, credible comparative data showing progress, and shared experiences of patient benefit.